2016
DOI: 10.1093/carcin/bgw102
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a radiation biomarker into modeling of thyroid carcinogenesis and post-Chernobyl risk assessment

Abstract: Strong evidence for the statistical association between radiation exposure and disease has been produced for thyroid cancer by epidemiological studies after the Chernobyl accident. However, limitations of the epidemiological approach in order to explore health risks especially at low doses of radiation appear obvious. Statistical fluctuations due to small case numbers dominate the uncertainty of risk estimates. Molecular radiation markers have been searched extensively to separate radiation-induced cancer case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…So far, no reliable molecular signature has been established. An analysis of Chernobyl cases reported that CLIP2 , which is located on chromosome 7q11.23, is specifically amplified in a subset of cases compared to unexposed PTCs, and that on immunohistochemistry, a significant difference in the level of protein expression is observed ( 39 ). Further studies, including analyses with more advanced technologies such as next-generation sequencing, are necessary to identify molecular signatures associated with radiation exposure.…”
Section: Genetic Alterations In Thyroid Cancer Resulting From Radiatimentioning
confidence: 99%
“…So far, no reliable molecular signature has been established. An analysis of Chernobyl cases reported that CLIP2 , which is located on chromosome 7q11.23, is specifically amplified in a subset of cases compared to unexposed PTCs, and that on immunohistochemistry, a significant difference in the level of protein expression is observed ( 39 ). Further studies, including analyses with more advanced technologies such as next-generation sequencing, are necessary to identify molecular signatures associated with radiation exposure.…”
Section: Genetic Alterations In Thyroid Cancer Resulting From Radiatimentioning
confidence: 99%
“…In the genesis of oncological diseases, a significant role may belong to irradiation of the population (Kaiser et al, 2016). Mean total doses of internal and external irradiation of the population of the affected regions of Zhytomyr Oblast equaled 1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the investigation of papillary thyroid carcinoma from a cohort revealed an overexpression of the CLIP2 gene among young patients exposed to the post-Chernobyl radioiodine fallout at a very young age [ 19 ]. More recently, mechanistic models were proposed to explore the impact of radiation on the molecular landscape of papillary thyroid carcinoma [ 20 , 21 ]. The findings point to a function of CLIP2 as a driver gene in radiation-induced papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%